Analisis Pengaruh Indeks Pembangunan Manusia (IPM), Pertumbuhan Ekonomi (PDRB) dan Tingkat Pengangguran Terbuka (TPT) terhadap Tingkat Kemiskinan di Provinsi Gorontalo - Pratiwi Utami; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims ti analyze the effect of the Human Development Index (HDI), Gross Regional Domestic Product (GRDP), and Open Unemployment Rate (OUR) on the poverty rate in Gorontalo Province. The study uses panel data from six districts/cities over the period 2017–2024 and is analyzed using panel data regression methods. Based on the results of the Chow test, Hausman test, and Lagrange Multiplier test, the best model used is the Fixed Effect Model (FEM). The analysis results show that simultaneously, the three independent variables have a significant effect on the poverty rate. However, partially, only the GRDP variable has a negative and significant effect on poverty. Meanwhile, the HDI and OUR variables show a negative but statistically insignificant effect on the poverty rate in Gorontalo Province.